A method for designing complex biosecurity surveillance systems: detecting non‐indigenous species of invertebrates on Barrow Island. Issue 5 (6th May 2013) - Whittle, Peter J. L.; Stoklosa, Richard; Barrett, Susan; Jarrad, Frith C.; Majer, Jonathan D.; Martin, P. A. J.; Mengersen, Kerrie; Burgman, Mark
Abstract Aim We developed a new method to design objective, risk‐based surveillance systems for non‐indigenous species of invertebrates, vertebrates and plants, which might be introduced to a natural area through an industrial project; here, we provide the invertebrate case study. The method addresses issues common to complex surveillance design problems: a statistical standard (e.g. power); information gaps; multiple targets of unclear identity; a large surveillance area of heterogeneous risk of invasion; integrating multiple sources of surveillance data; optimizing for cost. Location Barrow Island, Western Australia. Methods We mapped the surveillance area for risk to target surveillance activities. An expert group identified a set of exemplar species and identified and characterized a set of detection methods for each, such that all potential invaders would be detected. We devised multi‐element surveillance systems to detect each exemplar to the design power (0.8), then integrated them to a single system that was optimized for cost. Results The surveillance system was deployed on the island to specification over 1 year, then reviewed for redesign in a second period. Main conclusions The new method provided practical, risk‐based surveillance system designs that met application requirements and overcame complex issues common to many surveillance applications. A review of experiences from surveillance in the first year led to practical improvements and design efficiencies.